Beyond Job Matching: Creating Positive Experiences at Medan Tourism Polytechnic Job Fairs - Hutasuhut, Efriza Monalisa; Jamardua Haro (HM Publisher, 2024)
The evolving tourism industry demands that job fairs at Tourism Polytechnics transcend their traditional role of mere job matching. These events now present a unique opportunity to craft positive and holistic experiences that benefit both job seekers and employers, thereby contributing to the overall enhancement of the tourism workforce. The significance of this shift is underscored by the recognition that job seekers today are not solely in pursuit of employment; they aspire to gain industry insights, access career development avenues, and establish connections with seasoned professionals. This research adopts a robust mixed-methods approach, integrating surveys, interviews, and observational data gathered at tourism polytechnic job fairs. The study's findings illuminate the criticality of cultivating a positive and enriching experience at Tourism Polytechnic job fairs. The research underscores the necessity of establishing a welcoming and informative environment, fostering meaningful dialogues between job seekers and employers, and presenting career development resources that resonate with the aspirations of attendees. The data also brings to light certain challenges, such as the need to bolster employer participation and refine post-event follow-up mechanisms. In conclusion, the research culminates in the assertion that tourism polytechnic job fairs possess the capacity to significantly elevate the job-seeking experience by furnishing invaluable resources and avenues for career progression.